Oxidative esterification via photocatalytic C–H activation. Issue 1 (12th October 2015) - Verma, Sanny; Baig, R. B. Nasir; Han, Changseok; Nadagouda, Mallikarjuna N.; Varma, Rajender S.
Abstract : Direct oxidative esterification of alcohol via photocatalytic C–H activation has been developed using VO@g-C3 N4 catalyst; expeditious esterification of alcohol occurs under neutral conditions using visible light. Abstract : Direct oxidative esterification of alcohol via photocatalytic C–H activation has been developed using VO@g-C3 N4 catalyst; an expeditious esterification of alcohols occurs under neutral conditions using visible light as the source of energy.